Impact of organic inputs and transplanting dates on foraging mode of honey bees in radish (Raphanus sativus L.) - Divya Prakash Singh; S. C. Verma; Navjot Singh Kaler; Anil Kumar (Annals of Agricultural Research, 2022)
An investigation was carried out during two consecutive years (2014-15 and 2015-16) at Research Farm of Department of Seed Science and Technology, Dr. Y. S. Parmar University of Horticulture and Forestry, Nauni, Solan-273230. The experiment was conducted on effect of different organic inputs like vermicompost, FYM, Azotobactor, PSB and PGPR and transplanting dates on foraging mode of honey bees in radish (Raphanus sativusL.). The transplanting was done on three different dates during both years. There were seven treatments including control and each treatment was replicated thrice. The data was analysed in factorial randomized block design. The study revealed that among the organic treatments, foraging speed of honey bees was higher 7.66, 7.09, 6.85 second/flower with T6 : Vermicompost @ 50 q/ha) + Azotobacter root dip @2.5 Kg/ha + PSB root dip @ 2.5 Kg/ha + NSKE (5%) on I, IIand III dates of transplanting, respectively which was statically at par with T5 : FYM @100q/ha +Azotobacter root dip @ 2.5 Kg/ha + PSB root dip @ 2.50 Kg/ha +NSKE (5%) and both the treatments were statically at par with T7 i.e. control. Foraging rate of honey bees was higher 6.60, 6.34, 5.21 number of flowers visited by honey bees/minute on I, IIand III dates of transplanting, respectively at 1200 h. Foraging speed of honey bees was higher 7.40, 6.90, 6.82 on IIIand III dates of transplanting, respectively at 0900 h. Foraging rate of A. cerana was higher (I: 5.96; II: 5.73; III:4.67) then A. mellifera (I: 4.66; II: 4.56; III: 4.53). Foraging speed of A. cerana was higher (I: 7.32; II: 6.73; III:6.64) then A. mellifera (I: 6.29; II: 6.27; III: 6.21).